Reducing Lumbar Spine Vertebra Fracture Risk With an Adaptive Seat Track Load Limiter - Östling, Martin; Lundgren, Christer; Lubbe, Nils; Pipkorn, Bengt (Frontiers in Future Transportation, 2022)
In future fully automated vehicles, sleeping or resting will be desirable during a drive. While a horizontal position currently appears infeasible, a relaxed seating position with a reclined seatback and an inclined seat pan is possible. However, the inclined seat pan increases the forces and moments acting on the lumbar spine of the occupant and thereby the risk of lumbar vertebra fractures in a frontal crash. An energy management system integrated in the longitudinal seat adjustment (a seat track load limiter: STLL) which can reduce this risk should be investigated. Evaluating the injury reduction potential of a new restraint system it is important to include variations in both occupant size and crash severity to avoid the risk for sub-optimizing. Restraint systems addressing these variations are normally referred to as adaptive restraint systems. The first objective of the study is to develop an activation strategy (adaptive release time of the STLL) for different crash severities and occupant sizes, making full use of the available stroke distance without bottoming out the STLL. The second objective is to evaluate the potential of the adaptive STLL to reduce the risk of lumbar vertebra fractures by comparing it to 1) a fixed seat and 2) a passive version of the STLL. Simulated frontal impacts were performed with two male SAFER Human Body Models (HBMs) as occupant surrogates: mid-sized (80 kg and 1.8 m) and large (130 kg and 1.9 m). Three severity levels were evaluated: low (40 km/h), medium (50 km/h), and high (56 km/h) impact speeds. The fracture risk was evaluated for the five lumbar vertebrae (L1–L5) in three different seat conditions: (1) a seat fixed to the sled, (2) a passive STLL which moves when a given force is exceeded, and (3) an adaptive STLL which moves at a time that depends on the occupant mass and crash pulse severity. The risk for lumbar vertebra fracture increased with crash severity, while HBM size had no effect on risk. For all conditions, the passive STLL reduced injury risks compared to the fixed seat, and the adaptive STLL reduced risk even further.